Проблеми регіональної безпеки в країнах Південно-Східної Азії: міжнародна співпраця та механізми її здійснення - Підберезних, Інна; Podbereznykh, Inna (My University, 2015)
У статті розглянуто проблеми формування основних принципів безпеки в районі Південно-Східної Азії, його співпрацю зі США в цій сфері, перспективу їх розвитку; визначено чинники формування міжнародних відносин у зміцненні авіаційних та морських зв’язків безпеки в ПСА; проаналізовано потенційні можливості модернізації структури системи безпеки в цьому регіоні.The paper addresses the problem of formation the basic safety principles in the area of Southeast Asia, its cooperation with the US in this area, the prospect of their development; definits the factors of shaping the international relations to strengthen aviation and maritime security ties in Southeast Asia; analyzes the potential abilities of restructuring security system in this area. The collapse of the bipolar system caused significant transformations in world’s political and strategic balance of powers.
Problems of Safety are in the Countries of South-east Asia: International Cooperation and Mechanisms of her Realization
Keywords: Асоціація країн Південно-Східної Азії (АСЕАН); Азійсько-Тихоокеанський регіон (АТР); міжнародне співробітництво; регіональна безпека; регіональна інтеграція; ASEAN; Asia-Pacific; international cooperation; regional security; regional integration